Opioids inhibit endothelin-mediated DNA synthesis, phosphoinositide turnover, and Ca2+ mobilization in rat C6 glioma cells - Barg, J (Society for Neuroscience, 1994)
Opioid agonists inhibit DNA synthesis in C6 rat glioma cells that express opioid receptors, induced by desipramine (DMI). This inhibition was not observed in cells that were not treated with DMI, and thus did not express opioid-binding sites. Endothelin, a known mitogen, increased thymidine incorporation dose dependently (up to 1.7-fold) in DMI-treated C6 cells. This increase was reversed by an anti-idiotypic antibody to opioid receptors, Ab2AOR, which has opioid agonist properties. The opioid antagonist naltrexone blocked the inhibition caused by Ab2AOR. Endothelin also stimulated phosphoinositide (PI) turnover and this effect was inhibited by morphine (50%) or by Ab2AOR (72%) in DMI-treated but not in DMI-untreated C6 cells. These actions of morphine and Ab2AOR were reversed by naltrexone. The inhibition of PI turnover and of thymidine incorporation by Ab2AOR or morphine was insensitive to pertussis toxin (PTX). Since PI turnover is known to induce Ca2+ mobilization, it was of interest to examine the effects of the applied opioids on intracellular Ca2+ concentrations. Endothelin increased the concentration of cytosolic free Ca2+ in the cells while Ab2AOR, morphine, and beta-endorphin reversed the endothelin-induced Ca2+ mobilization in DMI-treated but not in DMI-untreated C6 cells. The effect of these agonists was also blocked by naltrexone. The results indicate that glial cells can be a target of an opioid receptor- mediated antimitogenic action and that an abatement in PI turnover and Ca2+ mobilization may be associated with this mechanism.